Elevational patterns of soil organic carbon and its fractions in tropical seasonal rainforests in karst peak-cluster depression region - Zhang, Bei; Xu, Chaohao; Zhang, Zhonghua; Hu, Cong; Zhong, Chaofang; Chen, Siyu; Hu, Gang (Frontiers in Plant Science, 2024)
Karst ecosystems, especially tropical karst forests, are crucial to the global carbon cycle. In mountainous and hilly areas, elevation-related changes in environment and vegetation often lead to shifts in the accumulation and decomposition of soil organic carbon (SOC). However, the elevational patterns and influencing variables of SOC and its fractions in tropical karst forest ecosystems remain largely unexplored. Here, we analyzed the elevational patterns of SOC and its fractions in the topsoil and subsoil in the tropical seasonal rainforests within typical peak-cluster depression region of Southwest China. Our results indicated that the SOC content was highest at 400 m asl, which was significantly higher than that at 200 m asl (p < 0.05). Overall, SOC content demonstrated an increasing trend with rising elevation. Additionally, SOC content was significantly higher in the topsoil compared to the subsoil (p < 0.05). The majority of SOC fractions exhibited an increase with elevation but decrease with soil depth. Notably, only water-soluble organic carbon (WSOC) displayed a decrease with elevation. Meanwhile, recalcitrant organic carbon (ROC, 54.27%), particulate organic carbon (POC, 30.19%), and easily oxidizable organic carbon (EOC, 16.95%) were the main SOC fractions. Labile organic carbon (LOC) in the karst forest soil was predominantly composed of EOC and POC. Correlation analysis unveiled significant positive correlations between SOC and certain fractions with elevation, soil total nitrogen, and exchangeable magnesium. Conversely, significant negative correlations were observed with soil bulk density (SBD), soil total phosphorus, and litter phosphorus (Litter P). Redundancy analysis indicated that elevation, SBD, and Litter P were the main environmental variables influencing shifts in SOC and its fractions. Structural equation models showed that SOC was primarily directly impacted by soil properties but indirectly impacted by elevation. ROC was mainly associated with the direct effects of soil properties and litterfall, although elevation exerted a substantial impact through indirect pathways. Moreover, LOC was predominantly influenced by the direct impact of soil properties. Therefore, this study demonstrates that SOC and its fractions are strongly influenced by elevation in karst peak-cluster depression regions and have important implications for forest management and sustainable ecosystem development in these regions.